2021
DOI: 10.30741/wiga.v11i1.577
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee, Board, and Audit Report Lag

Abstract: Effect of corporate governance being the crucial issue in growing process of audit financial statement in order to decrease audit report lag. Some of previous studies stated that correlation between corporate governance and audit report lag is not consistence. That is why, this study used variable control as firm and auditor characteristics in order to find out the effect of audit committee and board characteristics to audit report lag. The variable independent consist of audit committee size, audit committee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…The result of Rahmansyah, Wardayati and Miqdad, (2021) revealed that only board size has significant effect to audit report lag. The study of Firnabti and karmudiandri, (2020) discovered was also consistent and also find a similar result to Rahmansyah et. al., (2021).…”
Section: Discussion Of Findingsmentioning
confidence: 97%
“…The result of Rahmansyah, Wardayati and Miqdad, (2021) revealed that only board size has significant effect to audit report lag. The study of Firnabti and karmudiandri, (2020) discovered was also consistent and also find a similar result to Rahmansyah et. al., (2021).…”
Section: Discussion Of Findingsmentioning
confidence: 97%
“…Sehingga dalam pertemuan tersebut tidak ditemukan adanya informasi terkait laporan keuangan dan proses audit, sehingga tidak ditemukan adanya permasalahan dalam laporan keuangan dana yang akan menjadi kendala dalam proses audit. Oleh karena itu, banyak atau sedikitnya jumlah rapat dewan tidak dapat memperpendek atau memperpanjang audit report lag dalam satu tahun (Rahmansyah et al, 2021).…”
Section: Pengaruh Rapat Dewan Direksi Terhadap Audit Report Lagunclassified
“…Ukuran Komite Audit (ACSIZE) dihitung melalui logaritma natural perbandingan total aset dengan jumlah seluruh anggota komite audit (Rahmansyah et al, 2020;Suripto, 2012).…”
unclassified